Development of Designer Transcription Activator-Like Effector-Based Plant Growth Regulator for Higher Yield in Rice - Tang, Yongchao; Wang, Chunlian; Wang, Fujun; Li, Man; Fang, Yanli; Ji, Zhiyuan; Zhao, Kaijun (Frontiers in Plant Science, 2022)
Recent studies have shown that reprogramming of gene expression in a genome can induce the production of proteins enabling yield increase. The transcription activator-like effectors (TALEs) from several species of bacterial Xanthomonas have been extensively studied, and a series of research tools, such as genome editing tool TALENs and gene expression activators, have been developed based on the specific protein–nucleic acid recognition and binding mechanisms of TALEs. In this proof-of-principle study, we designed and constructed a designer TALE (dTALE), designated as dTALE-NOG1, to specifically target the promoter of OsNOG1 gene in rice, and demonstrated that this dTALE can be used as a new type of plant growth regulator for better crop growth and harvest. In doing so, the dTALE-NOG1 was transferred into the non-pathogenic Xanthomonas oryzae pv. oryzae (Xoo) strain PH to generate a genetically engineered bacteria (GEB) strain called PH-dtNOG1. Functional verification showed that dTALE-NOG1 could significantly induce the expression of OsNOG1. By spraying cell suspension of PH-dtNOG1 on the rice plants during the tillering stage, the transcription level of OsNOG1 was highly enhanced, the grain number of rice plants was increased by more than 11.40%, and the grain yield per plant increased by more than 11.08%, demonstrating that the dTALE-NOG1 was highly effective in enhancing rice yield. This work provided a new strategy for manipulating agronomical traits by reprogramming gene expression in a crop genome.